Common Periodontal Diseases of Children and Adolescents - Hayat Al-Ghutaimel; Hisham Riba; Salem Al-Kahtani; Saad Al-Duhaimi (Hindawi Limited, 2014)
Background. Since 2000, studies, experiments, and clinical observations revealed high prevalence of periodontal diseases among children and adolescents. Therefore, this paper was designed to provide an update for dental practitioners on epidemiology, microbiology, pathology, prevention, diagnosis, and treatment of periodontal diseases in children and adolescents. Methods. This paper reviews the current literature concerning periodontal diseases in pediatric dentistry. It includes MEDLINE database search using key terms: "periodontal diseases in children," "Periodontal diseasesin adolescents," "periodontal diseases risk factors," "microbiology of periodontal diseases," "classification of periodontal diseases," "epidemiology of periodontal diseases," and "treatment of periodontal diseases." Articles were evaluated by title and/or abstract and relevance to pediatric dentistry. Sixty-five citations were selected by this method and by the references within the chosen articles. A review of the comprehensive textbooks on pediatric dentistry and periodontology was done. Some recommendations were based on the opinions of experienced researchers and clinicians, when data were inconclusive.